Educational Entrepreneurship in Islamic Schools: Strategies for Innovation, Creativity, and Organizational Excellence - Mahmud Abdul Ghofur; Nur Annisa Almaidah; Sidiq Purnomo (International Journal of Science and Environment (IJSE), 2026)
This study aims to conduct an in-depth analysis of educational entrepreneurship strategies implemented to foster innovation, creativity, and organizational excellence in Islamic educational institutions. This study employs a qualitative approach using a case study design to analyze educational entrepreneurship strategies in fostering innovation, creativity, and organizational excellence at MA Roudlotul Muta'allimin Simbar Tampo Cluring, Banyuwangi. The research was conducted over two weeks and involved eight observation sessions with the madrasah principal, vice principal, teachers, educational staff, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and drawing conclusions. Data validity was ensured through triangulation and member checking. The results of the study indicate that the implementation of educational entrepreneurship at MA Roudlotul Muta'allimin Simbar Tampo Cluring, Banyuwangi, is carried out through three main strategies. First, entrepreneurial leadership plays a role in building a culture of innovation through empowerment, participation, and openness to new ideas, thereby fostering the creation of innovative programs. Second, the development of creativity among teachers and students is achieved through participatory programs that create a collaborative and productive learning environment. Third, the establishment of an adaptive organizational culture through the values of cooperation, responsibility, and continuous learning enhances the quality of the institution and strengthens its organizational excellence. These findings confirm that the synergy between entrepreneurial leadership, participatory creativity, and an adaptive organizational culture serves as a crucial foundation for improving the quality and competitiveness of Islamic educational institutions.